Microstructure and Properties of plasma spray coatings prepared from Ti-Zr-Ni Quasicrystalline powders - Seok, Hyun Kwang; Kim Yu Chan; F. Prima; Eric Fleury (PROGRESS IN POWDER METALLURGY, PTS 1 AND 2, 2006)
This works deals with the deposition of Ti-Zr-Ni icosahedral quasicrystalline powders by low vacuum plasma spray technique and the performances of the resulting coating layers. The microstructure of the coatings, as analyzed by X-ray diffraction and TEM techniques, consisted of nanometer-sized W-Ti50Zr35Ni15 1/1 cubic approximant and TiZrNi Laves phases as well as a low volume fraction of submicrometer-sized ZrO2 phase. The absence of the icosahedral phase in the coating layers was explained by the loss of Ti during plasma spraying. The shift in the composition and the presence of the ZrO2 phase within the coating layers are believed to be responsible for the reduced microhardness and corrosion performances evaluated by electrochemical tests in a Hanks' Balance Salt Solution at 37 degrees C.
Keywords: Ti-Zr-Ni; Quasicrystalline; plasma spray coating; microhardness; corrosion; titanium